Phenotypic and molecular variation in the green and black poison-dart frog Dendrobates auratus (Anura: Dendrobatidae) from Costa Rica - Lisa D Patrick; Mahmood Sasa (Revista de Biología Tropical, 2009)
The green and black poison-dart frog Dendrobates auratus exhibits high intraspecific variation in hue color and pattern throughout its range, making it a very popular species in the pet trade. We analyzed the correspondence between color variation and molecular variation of D. auratus from Costa Rica using RAPD analysis. Twenty-six random primers were analyzed for variation in 99 individuals from seven populations. Color pattern was scored from digital images of the dorsal and ventral views. In general, frogs from the Caribbean coast had significantly more light coloration than black color but cannot be grouped by population based only on hue pattern. Only 3 RAPD primers were found to be polymorphic, representing a total of 16 loci. Most of the molecular variation encountered here occurs within populations, thus making unclear the degree of population structure and differentiation. Further examination of COI mtDNA sequences from our samples also supports these results. Partial Mantel correlations suggested that the pattern of molecular variation is not congruent with the variation in color pattern in this species, an outcome that is discussed in terms of phenotypic evolution. Rev. Biol. Trop. 57 (Suppl. 1): 313-321. Epub 2009 November 30.